2019
DOI: 10.11648/j.ijcoms.20190501.16
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Pathways and Surgical Approaches in the Fractures of the Frontal Sinus

Abstract: Fractures of the frontal sinus are part of the fractures of the border between the facial and the cranial regions.They cause both aesthetic and vital problems, but also functional, requiring rapid and global care in a multidisciplinary setting. The document provides a descriptive and cross sectional study with prospective data collection, conducted in the department of Maxillofacial and Aesthetic Surgery of the Mohammed 6 Teaching Hospital of Marrakech, describe describe 18case operated for frontal sinus fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…The approach can be made through the traumatic wound (tans-cicatricial), as was the case in the present study in 25% of patients. This frequency was higher than that reported by Mabika et al [16] and Mahran et al [5], who reported frequencies of respectively 16.7% and 8.5% of cases. The trans-cicatricial approach allows easy, direct and non-invasive exposure of the frontal sinuses, but has the disadvantage of scarring which can be minimised by respecting the skin tension lines [8].…”
Section: Discussioncontrasting
confidence: 69%
See 4 more Smart Citations
“…The approach can be made through the traumatic wound (tans-cicatricial), as was the case in the present study in 25% of patients. This frequency was higher than that reported by Mabika et al [16] and Mahran et al [5], who reported frequencies of respectively 16.7% and 8.5% of cases. The trans-cicatricial approach allows easy, direct and non-invasive exposure of the frontal sinuses, but has the disadvantage of scarring which can be minimised by respecting the skin tension lines [8].…”
Section: Discussioncontrasting
confidence: 69%
“…A total of 102 cases of frontal sinus fractures were reported, giving an annual average of 34 cases. This average is higher than that reported by Mabika et al [16] and Mahran et al [5], who reported respective averages of 12 and 25.6 cases per year. The high frequency of frontal sinus fractures in this study could be explained by the fact that the data were collected in two departments (maxillofacial and neurosurgery) and by the predominance of RTAs (90.20%) frequently involving drivers of two-wheeled machines (98.20%) without helmets.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations